Games for language learning - Wright, Andrew (Cambridge University Press, 1983)
Games provide meaningful and enjoyable language practice at all levels and for all age groups. They can be used to practise any of the skills - speaking, listening, reading and writing - at any stage of the learning process, from controlled repetition through guided practice to free expression. To enable teachers to select the activities most suitable for their needs, precise information is provided, both at the beginning of each game and in the summary chart, about the language content, the skills to be practised, the level, the degree of teacher-control, and the time and materials required. Clear advice is given on preparation and classroom procedure, with many illustrations and examples